The distribution law and coupling factors of debris flows in the G318 Linzhi–Lhasa section of the Sichuan–Tibet traffic corridor - He, Na; Song, Yabing; Hu, Guisheng; Yang, Zhiquan; Fu, Qixuan; Gurkalo, Filip (Frontiers in Ecology and Evolution, 2023)
In recent years, debris flow disasters have occurred frequently along the highway, causing river blockages and road interruptions, which seriously threaten the safety of people's lives and property. Highway G318 is an important throat project linking Sichuan and Tibet, at the same time it is an important channel for the economic development of Sichuan and Tibet and the transportation of national defence materials. Taking the Linzhi-Lhasa Section of Highway G318 as an example, this paper analyses the distribution law and coupling factors characteristics of debris flows in the study area (under its topographical, hydro-meteorological, geological and structural conditions) by using remote sensing interpretation, field surveys and mathematical statistics. The research shows that: (1) The types and quantity of debris flows in the region show statistical laws under the factors of slope, slope aspect, drainage area, and gradient of the gully. The vegetation coverage in the upper reaches of the Niyang River valley gradually decreases, and the average debris flow disaster density is 0.529/km which is the most densely distributed area of debris flow. (2) The distribution density of regional debris flows in narrow valleys is greater than those in wide valleys and those in the Niyang River basin are greater than those in the Lhasa River basin. (3) By comparing the tectonic geological map and the debris flow distribution map, it was found that the debris flow distribution is obviously controlled by faults and 71% of the debris flow basins have faults. (4) There is a significant positive correlation between the gradient of the material source area and the gradient of the debris flow gully, a close positive correlation between the rainfall and the fault density, and a close negative correlation between the average gradient and the drainage area. By studying the distribution law of regional debris flow, this paper provides strong support for regional debris flow prevention and related research.